Optimization of task scheduling for computing reuse in computing power network - Yunxiao MA; Zhonghui WU; Zuyun XU; Lujie ZHONG; Changqiao XU (Tongxin xuebao)
To cope with the challenges posed by the future explosive growth in computing power demand, computing reuse technology was introduced into the computing power network to reduce service latency and computational resource consumption by reusing the results of computational tasks.Based on this, a service federation-based context-aware online learning algorithm was proposed.First, the reuse index was designed to reduce the extra lookup latency.Then, online learning was performed based on the service federation mechanism to make computational task scheduling decisions according to contextual information and historical experience.The experimental results show that the proposed algorithm outperforms the baseline algorithms in terms of service latency and computational resource consumption.